Using the framework of entrustable professional activities to promote reflective practice among medical students - Shrivastava, Saurabh RamBihariLal; Bobhate, Prateek Sudhakar; Mendhe, Harshal Gajanan (Indian Journal of Community Health, 2025)
Entrustable Professional Activities (EPAs) have been employed across heterogeneous settings in training medical students and preparing them to provide quality-assured clinical care to patients. In the field of medical education and healthcare delivery, reflective practice refers to the process of critical analysis of own’s experiences and actions in a systemic manner to not only learn from these but even take remedial measures to ameliorate performance in the future. The designed rubrics of milestones for individual EPAs specifically provide clear tasks and expectations from students, and based on their performances, they can reflect and even make efforts to align their progress. The decision to use EPAs to promote reflective practice in any institution has been linked with multiple challenges, nevertheless, there have been some concerns that need to be timely addressed to draw meaningful outcomes and benefit students. In conclusion, reflective writing has been associated with multiple benefits to students and makes them self-directed learners. The need of the hour is to use the framework of entrustable professional activities to promote the practice of reflective writing among medical students.